Influence of mentoring on learning outcomes of pioneering school-based 'international award for young people' programme in Malaysia - Lee, Kwan Meng (2012)
The youth resource in Malaysia comprising of about 45% of its general population needs to be translated into being the nation’s human capital through the formal, non-formal, and informal learning approaches. One approach is the practice of mentoring where the young people are partnered with adult mentors who coach, guide, and facilitate their development. Mentoring has been found in many studies to facilitate positive youth development effectively. The question now is the extent mentoring and its practices contribute to youth learning, and influence learning outcomes. The main purpose of this study then is to determine the extent of mentoring practice among school-based participants of the ‘International Award for Young People’ (IAYP) programme in Malaysia and its influence on their learning outcomes by determining the relationship and predictability of mentoring practices with learning outcomes in knowledge, attitude, and skill. The study was a corelational design. The respondents comprise all 90 schoolbased population who participated in the Award programme of Yayasan Saad College in 2011 who were then pursuing their silver and gold awards when the study was conducted. A survey questionnaire was administered to the participants where the instrument include question items on the practices of mentoring comprising of mentor relationship development, mentor bonding,coaching, facilitation, guiding, reflecting, and learning experientially. This mentoring practice was the independent variable, whereas, the learning outcomes of knowledge, attitude, and skill were the dependent variables. This instrument that was employed was pilot tested, and then tested for reliability. It was also validated for check dimension through exploratory factor analysis (EFA). The findings of the study show that there are strong relationships between facilitating, coaching with the three learning outcomes, whereas, mentor establishment and bonding and reflecting has no relationship with learning. However, it was learning outcomes related to skill that was mostly contributed by the mentoring facilitating. Nonetheless, the study shows that facilitating has a 49%, 50%, and 45% influences on knowledge, attitude, and skill learning outcomes respectively; while coaching has influence only on knowledge and attitude learning outcomes. It can be concluded that though learning outcomes occur, it was not through the mentoring relationship, but through the facilitation and coaching. The mentoring relationship instead established the foundation for the practices of learning to be enabled, while reflecting was the learning aspect that was internalized to learn experientially. The facilitation and enabling of learning then contribute towards the inculcation of self-directed, andragogical form of learning where the mentee becomes self-motivated learners. Mentoring practices thus an approach to facilitate learning in co-curricular activities in schools in the context of nonformal learning. From this study, the findings therefore demonstrate that mentoring could complement holistic education of the young people. It can be concluded that in the IAYP programme, the participants have benefited in some ways through the mentoring practices, and support Bandura’s Social learning and Social cognitive theories. In this way, the young people learned through role modeling to reinforce their self-efficacy towards their personal and character development.